Hospital Website Rankings in the United States: Expanding Benchmarks and Standards for Effective Consumer Engagement - Huerta, Timothy R; Hefner, Jennifer L; Ford, Eric W; McAlearney, Ann Scheck; Menachemi, Nir (JMIR Publications, 2014)
BackgroundPassage of the Patient Protection and Affordable Care Act (ACA) increased the roles hospitals and health systems play in care delivery and led to a wave of consolidation of medical groups and hospitals. As such, the traditional patient interaction with an independent medical provider is becoming far less common, replaced by frequent interactions with integrated medical groups and health systems. It is thus increasingly important for these organizations to have an effective social media presence. Moreover, in the age of the informed consumer, patients desire a readily accessible, electronic interface to initiate contact, making a well-designed website and social media strategy critical features of the modern health care organization. ObjectiveThe purpose of this study was to assess the Web presence of hospitals and their health systems on five dimensions: accessibility, content, marketing, technology, and usability. In addition, an overall ranking was calculated to identify the top 100 hospital and health system websites. MethodsA total of 2407 unique Web domains covering 2785 hospital facilities or their parent organizations were identified and matched against the 2009 American Hospital Association (AHA) Annual Survey. This is a four-fold improvement in prior research and represents what the authors believe to be a census assessment of the online presence of US hospitals and their health systems. Each of the five dimensions was investigated with an automated content analysis using a suite of tools. Scores on the dimensions are reported on a range from 0 to 10, with a higher score on any given dimension representing better comparative performance. Rankings on each dimension and an average ranking are provided for the top 100 hospitals. ResultsThe mean score on the usability dimension, meant to rate overall website quality, was 5.16 (SD 1.43), with the highest score of 8 shared by only 5 hospitals. Mean scores on other dimensions were between 4.43 (SD 2.19) and 6.49 (SD 0.96). Based on these scores, rank order calculations for the top 100 websites are presented. Additionally, a link to raw data, including AHA ID, is provided to enable researchers and practitioners the ability to further explore relationships to other dynamics in health care. ConclusionsThis census assessment of US hospitals and their health systems provides a clear indication of the state of the sector. While stakeholder engagement is core to most discussions of the role that hospitals must play in relation to communities, management of an online presence has not been recognized as a core competency fundamental to care delivery. Yet, social media management and network engagement are skills that exist at the confluence of marketing and technical prowess. This paper presents performance guidelines evaluated against best-demonstrated practice or independent standards to facilitate improvement of the sector's use of websites and social media.